2006
DOI: 10.1210/jc.2006-1605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levo-Thyroxine Replacement on Non-High-Density Lipoprotein Cholesterol in Hypothyroid Patients

Abstract: This study is the first to show that L-T4 replacement may reduce serum concentrations of non-HDL-C in patients with hypothyroidism. The study also suggests that such altered serum concentrations of non-HDL-C in hypothyroidism may be related to the disturbed metabolism of low-density lipoprotein, remnant lipoprotein, and Apo B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 21 publications
6
39
0
4
Order By: Relevance
“…In cases of hypothyroidism, how the serum Lp(a) levels are influenced by thyroid hormone remains unknown and contradictory results on the effect of thyroid hormone replacement on serum Lp(a) levels have been reported [6][7][8][9][10][11][12][13]. Although an altered lipid profile is frequently observed in patients with thyroid dysfunction, published data on the relationship between Lp(a) and thyroid status are controversial [14].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of hypothyroidism, how the serum Lp(a) levels are influenced by thyroid hormone remains unknown and contradictory results on the effect of thyroid hormone replacement on serum Lp(a) levels have been reported [6][7][8][9][10][11][12][13]. Although an altered lipid profile is frequently observed in patients with thyroid dysfunction, published data on the relationship between Lp(a) and thyroid status are controversial [14].…”
Section: Introductionmentioning
confidence: 99%
“…32 In another study, a significant reduction in the concentrations of total cholesterol, non-HDL and apo-B was found, but without significant changes in the serum concentrations of LDL, HDL cholesterol, TGL, apolipoprotein A-I, and Lp(a) after levo-thyroxine replacement. 33 The reduction in total cholesterol levels were inversely correlated with an increase in free T4 levels, but not correlated with changes in TSH levels.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, there was a positive correlation between the reduction in TSH and apoB-48, suggesting that L-T4 replacement therapy improves lipid abnormalities as well as thyroid function. Ito et al also reported that serum TC, non-HDL-C, LDL-C, apoB and RLP-C were markedly decreased after 3 months' treatment 41) ; therefore, it can be speculated that L-T4 replacement therapy might be effective to improve the impaired metabolism of CMR, as well as VLDL or LDL.…”
Section: Discussionmentioning
confidence: 99%